Práticas Culturais na Escola de Língua Japonesa da Associação Cultural e Esportiva Nikkey de Bastos - ACENBA - Araújo, Natália Vitória Feitosa (Brasil, 2022)
This paper aims to interpret the cultural practices carried out at the Japanese Language School of the Bastos Nikkei Cultural and Sports Association - ACENBA, located in the state of São Paulo, through participant observation. The importance of this research lies in the fact that there are few works related to the cultural practices involving the students of Japanese language education, and in this sense, it sought to present, initially, historical facts about the creation of the municipality by Japanese immigrants, the establishment of the Association, as well as the ACENBA school. Other sources were also used, such as a diary entry and photographs that helped in the construction of this study. As a theoretical reference, the postulates of Geertz (2008) were adopted, who establishes culture from the standpoint of interpretation of meanings. As a result, cultural practices in Bastos are directly linked to the awareness and appreciation of the space in which the people of Bastos live.